Superradiant emission from colour centres in diamond. Issue 12 (December 2018) - Angerer, Andreas; Streltsov, Kirill; Astner, Thomas; Putz, Stefan; Sumiya, Hitoshi; Onoda, Shinobu; Isoya, Junichi; Munro, William; Nemoto, Kae; Schmiedmayer, Jörg; Majer, Johannes
Abstract Superradiance is a fundamental collective effect where radiation is amplified by the coherence of multiple emitters1 . Superradiance plays a prominent role in optics (where it enables the design of lasers with substantially reduced linewidths2, 3 ) and quantum mechanics4, and is even used to explain cosmological observations such as Hawking radiation from black holes5 . Resonators coupled to spin ensembles6–8 are promising future building blocks of integrated quantum devices that will involve superradiance. As such, it is important to study its fundamental properties within such devices. Although experiments in the strong-coupling regime have shown oscillatory behaviour in these systems9, 10, a clear signature of Dicke superradiance has so far been missing. Here we explore superradiance in a system composed of a three-dimensional lumped element resonator in the fast cavity limit inductively coupled to an inhomogeneously broadened ensemble of nitrogen–vacancy centres. We observe a superradiant pulse being emitted a trillion times faster than the decay for an individual nitrogen–vacancy centre. This is further confirmed by the nonlinear scaling of the emitted radiation intensity with respect to the ensemble size. Our work provides the foundation for future quantum technologies including solid-state superradiant masers2 . Superradiance is reported from an ensemble of nitrogen–vacancy centres coupled to a microwave resonator in the fast cavity limit.